Support for instructional leadership : supervision, mentoring and professional development for U.S. school leaders : findings from the American School Leader Panel - Johnston, William R. (Writer on education); Kaufman, Julia H.; Thompson, Lindsey E. (Research report (Rand Corporation), 2016)
"An abundance of research suggests that effective school leaders are vital to promoting student outcomes in schools across the United States. Recognizing this, many state and local education agencies are motivated to develop a strong corps of highly qualified principals and assistant principals. Although a lot of emphasis is placed on recruitment and preservice training for new principals, many school districts are also working to support administrators once they are placed in schools. However, relatively little is known about the types of on-the-job supports currently available to school leaders, particularly on a national scale. This report presents findings from a Wallace Foundation -- funded survey of RAND's American School Leader Panel, a nationally representative sample of principals, regarding the quantity, content, and perceived quality of on-the-job support offered to them by their school districts. It focuses on three particular types of support -- supervision, mentoring, and professional development -- and investigates not only the prevalence of support for school leaders but also how this support reflects the role of leadership in instruction. In addition, responses of principals from small, midsize, and large school districts are examined to consider whether school leader support may look different depending on district size. This report was updated in October 2016. The current version provides estimates based on updated weights for a small percentage of the respondents. Weights were updated to account for infrequent misclassification in the assignment of school-level characteristics"--Publisher's description